Daya Gabung Galur Inbred, Penampilan dan Heterosis Hibrida Silang Tunggal Jagung (Zea mays L.): Daya Gabung Galur Inbred, Penampilan dan Heterosis Hibrida Silang Tunggal Jagung (Zea mays L.) - Oktakia, MS Dela; Hayati, PK Dewi; Sutoyo; Harnas, Hafid (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2025)
The utilization of superior hybrid varieties is pivotal in enhancing national maize productivity. Therefore, the continuous development of cultivars specifically adapted to distinct agroecosystems remains imperative. To that end, this study evaluated six inbred lines and 15 single-cross hybrids derived from a half diallel mating design to assess the combining ability of these inbred lines and examine the agronomic performance and heterotic expression manifested in the resulting hybrids. All genotypes, including the hybrids, inbred parents, and a check variety (P32), were tested using an RCBD with two replications in Nagari Situjuah, West Sumatra, Indonesia. The data were analyzed using F-tests followed by a planned LSD test with SAS software at the 5% significance level. PCA and path analysis were performed using RStudio, while GCA and SCA were analyzed using Diallel-SAS software. Results showed that the UZ 9 line performed the highest GCA for growth, flowering and yield-related traits. Hybrids UZ 3><UZ 9 (H2), P137-1><R2 (H14), and CLYN><R2 (H15) exhibited the best SCA values, coupled with superior agronomic performance, positive and high heterosis, heterobeltiosis, and standard heterosis for yield, achieving up to 11 tons hectare⁻¹, comparable to P32. PCA further supported these findings, which revealed that H2, H14, and H15 were associated with shorter flowering, harvesting periods and higher kernel yield. Path analysis identified kernel weight ear⁻¹ as the most influential variable affecting kernel yield hectare⁻¹. These findings highlight H2, H14, and H15 as promising hybrids with strong potential for further development and evaluation before release as new superior hybrid varieties.